Challenges and Barriers Recruitment of Professionals and Management Trainees in a Transitional Situation to the New Normal - Paing, Thein Ye; Tun, Sein Aung (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The purpose of this study is to find out the obstacles faced in recruiting professional and management trainees in the transition situation to the new normal. Competition in the global business world requires company management to be more concerned in managing human resources in it. However, in the new normal situation, several challenges and obstacles in professional recruitment are difficult to attract Candidates with the Right Qualifications, Incomplete Company-Related Information, Ineffective Channels Used, Limited Access to Required Devices and others. All recruitment processes including selection can be done online, the right solution during a pandemic.